Preoperative Risk Factors and Early Outcomes of Delirium in Valvular Open-Heart Surgery - Hulde, Nikolai; Zittermann, Armin; Tigges-Limmer, Katharina; Koster, Andreas; Weinrautner, Nicole; Gummert, Jan; von Dossow, Vera (The Thoracic and Cardiovascular Surgeon, 2022)
Background Compared with coronary artery bypass grafting surgery, data regarding postoperative delirium are scant in valvular open-heart surgery. Therefore, the goal of this retrospective study was to investigate the incidence, preoperative risk factors, and early outcomes of delirium in a large group of patients undergoing valvular open-heart surgery.Methods In 13,229 patients with isolated valvular or combined valvular and bypass surgery, the incidence of postoperative delirium was assessed until discharge. Independent risk factors of delirium were evaluated by multivariable logistic regression analysis. Moreover, we assessed the multivariable-adjusted risk of prolonged intensive care unit (ICU) stay (>48 hours) and in-hospital mortality in patients with delirium.Results Overall, the incidence of postoperative delirium was 8.4%. The incidence in patients experiencing a postoperative stroke or seizure was 23.1 and 29.7%, respectively. Twelve preoperative risk factors, mostly nonmodifiable, were independently associated with the risk of delirium, including advanced age, renal impairment, stroke, the need for emergency surgery, and severe preoperative anemia (hemoglobin < 9 g/dL). Postoperative delirium was associated with an adjusted odds ratio (OR) of prolonged ICU stay of 9.48 (95% confidence interval [CI]: 7.96–11.30). Adjusted in-hospital mortality was, however, significantly lower in patients with delirium versus patients without delirium (OR, 0.56; 95% CI: 0.38–0.83).Conclusion In valvular open-heart surgery, postoperative delirium is a frequent neurological complication that is associated with other postoperative neurological complications and several, mostly nonmodifiable, preoperative risk factors. Although postoperative delirium was associated with a significantly increased risk of prolonged ICU stay, this did not translate into an increased short-term mortality.
Keywords: delirium; etiology; valvular open-heart surgery; in-hospital mortality; risk factors